Conversion of food waste-derived lipid to bio-based polyurethane foam. (December 2021) - Lin, Carol Sze Ki; Kirpluks, Mikelis; Priya, Anshu; Kaur, Guneet
Abstract: Food waste contains complex nutrients such as carbohydrates, fats, proteins which could be broken down into simpler substrates such as sugars (e.g., glucose), lipids and proteins (e.g., free amino nitrogen). These components can be used for conversion into useful bio-based products such as chemicals, materials and fuels. This research aimed at the development of bio-based polyurethane (PU) materials using food waste-derived lipids. Since the quality of lipid plays an important role in polyol synthesis, optimal extraction procedures were developed to select the most appropriate method for polyol synthesis. From obtained lipids, two polyol synthesis methods were used, lipid transamidation with diethanolamine (DEOA or DEA) and lipid epoxidation and subsequent epoxy ring opening with trimethylolpropane. Bio-polyol obtained in transamidation reaction was used to obtain rigid PU foams with three different isocyanate indices of 130; 150 and 200 while bio-polyol form epoxy ring opening was used to obtain rigid PU foams with an isocyanate index of 150. The initial formulations were suitable to produce good quality rigid PU foam samples at a laboratory scale. The resultant rigid PU foams are promising for further studies and development of thermal insulation materials. Graphical abstract: Image 1